Human Capital Readiness, Learning Orientation, and InnovationPerformance in Creative Industries in Central Java - Ari Pradhanawati; Ngatno; Dewi, Reni (Jurnal Dinamika Manajemen, 2025)
This study aims to explore the effect of human capital readiness on innovation performance mediated by learning orientation. The research method used is quantitative with a survey approach. The research sample consisted of SMEs in the creative industries. Data were collected through surveys and processed using SEM_PLS. The results showed that human capital readiness has a positive and significant effect on innovation performance through learning orientation. This study shows that human capital readiness is the willingness of employees to actively participate in operational business processes, respond to market challenges, and drive innovation. This readiness requires the support of a supportive environment, such as a learning environment. Human capital readinesscan be fostered through a learning orientation that encourages employees to align the vision of the organization with the owner, to share knowledge, and to be open to change, ultimately fostering the growth of innovation.